2019
DOI: 10.3389/fmolb.2019.00141
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double Strand Breaks and Chromosomal Translocations Induced by DNA Topoisomerase II

Abstract: DNA double strand breaks (DSBs) are the most cytotoxic lesions of those occurring in the DNA and can lead to cell death or result in genome mutagenesis and chromosomal translocations. Although most of these rearrangements have detrimental effects for cellular survival, single events can provide clonal advantage and result in abnormal cellular proliferation and cancer. The origin and the environment of the DNA break or the repair pathway are key factors that influence the frequency at which these events appear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…For example, these may be related to spatial organisation of the genome, since recent studies have shown that loop anchors, bound by CTCF and cohesin, can mediate TOP2ß abortive breaks ( 9 , 42 , 43 ). To what extent this activity accounts for transcription-induced DSBs remains controversial ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, these may be related to spatial organisation of the genome, since recent studies have shown that loop anchors, bound by CTCF and cohesin, can mediate TOP2ß abortive breaks ( 9 , 42 , 43 ). To what extent this activity accounts for transcription-induced DSBs remains controversial ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining peptide can be then removed via the nuclease activity of the MRN complex ( 11 ) or by tyrosyl-DNA phosphodiesterase 2 (TDP2) ( 12 , 13 ). TDP2 cleaves the phosphotyrosyl bond between the topoisomerase peptide and the 5′ phosphate of the DNA, generating error-free ligatable ends that can be processed by the non-homologous end-joining (NHEJ) pathway ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, adjacent single-strand breaks in opposite strands may be converted to double strand breaks upon replication. DSBs are lethal unless repaired [27]. Ionizing radiations also induce clustered DNA damage in cells, which symbolize two, or more lesions formed within one or two helical turns of DNA and are in part responsible for the biological effects of ionizing radiation.…”
Section: Double Strand Breaks (Dsbs)mentioning
confidence: 99%